Operative Vaginal Delivery Is a Safe Option in Women Undergoing a Trial of Labor after Cesarean - Krizman, Erin; Grzebielski, Patricia; Antony, Kathleen M.; Sampene, Emmanuel; Shanahan, Matthew; Iruretagoyena, J. Igor; Bohrer, Justin (American Journal of Perinatology Reports, 2019)
Objective To compare outcomes of operative intervention in the second stage of labor during trial of labor after cesarean (TOLAC).Study Design A secondary analysis of the Maternal-Fetal Medicine Units Network cesarean section registry was conducted. Analysis was by first attempted mode of delivery.Results A total of 1,837 met inclusion criteria. Subjects in the operative vaginal groups (OVDs) were more likely to have a prior vaginal delivery (vacuum 34.2%; forceps 34.3%) than the repeat cesarean delivery (RCD) group (22.6%; p < 0.0001). Most OVD attempts were successful (forceps 90.4%; vacuum 92.6%). Neonatal morbidity was not different (12.1% forceps vs. 14.6% vacuum; 14.8% RCD). Maternal morbidity was highest among forceps deliveries (32.3 vs. 24.3% vacuum; 22.0% RCD, p = 0.0001). RCD was associated with surgical injury (2.7 vs. 0.7% forceps; 0% vacuum; p < 0.0001), endometritis (8.4 vs. 3.2% forceps, 1.2% vacuum; p < 0.0001), and wound complications (1.9 vs. 0.4% forceps; 0.3% vacuum; p = 0.006). OVD was associated with anal sphincter laceration (22.7% forceps, 15.5% vacuum; 0% RCD; p = 0.01).Conclusion The success rate of OVD is high in TOLAC with similar outcomes to RCD. Maternal composite outcomes were highest with forceps-assisted vaginal deliveries. However, considering overall morbidity, OVD in the second stage of labor in TOLAC is a reasonable, safe option in selected cases.
Keywords: trial of labor after cesarean; operative vaginal delivery; forceps delivery; vacuum-assisted delivery; vaginal birth; cesarean delivery